Relationships among Sleeplessness and Consumer Decision Making Styles: An Investigation with Vocational High School Students - Karakaya, Ertu?rul (British Journal of Marketing Studies, 2017)
Sleeplessness is a common problem in modern world. But importance and results of sleeplessness in terms of consumer behaviors is an overlooked research area. Related studies take into consideration the issue in terms of health. Moreover there is not seen a field research evaluating this issue from this viewpoint in Turkey. Present study is conducted to point out possible relationships among sleeplessness and major consumer decision making styles. In order to reach this objective, a survey is applied to vocational high school students which are selected with convenience sampling. Gathered data is analyzed with statistical data analyzing program and results are interpreted. According to data analysis results, it is concluded that sleeplessness is positively related with “indecision and confusion” and “careless decision”. Moreover it is depicted that sleeplessness is negatively related with “shopping avoidance”. In summary, the idea of sleeplessness can have important role in consumer behavior is supported. Although research results cannot be generalized to all consumers, the results give important insights for young consumers. By taking into consideration the research results, more effective marketing decisions can be made especially by marketers targeting consumers who are young and face sleeplessness problem. Further the sleeplessness can be researched by scholars in terms of other consumer behavior and attitude dimensions like; post-purchase consumer behaviors, consumer price sensitivity, search behavior, consumer attention to advertising etc.